Association between sitting time and high-sensitivity C - reactive protein level among obese women - Daud, Azlina; Jamal, Anis Fasehah; Shahadan, Siti Zuhaidah (2018)
Background Obesity is one of the biggest contributors of cardiovascular disease and risk of getting cardiovascular disease can be predicted by increasing high-sensitivity C-reactive protein (hs-CRP) level. Moreover, the prevalence of obesity in women was higher compared to men in adult age groups. High sitting time is also a risk factor for obesity among women. The objective of this study was to determine the association between sitting time per day and hs-CRP level among obese women. Methods A descriptive cross-sectional study was conducted on 68 obese women from Kuantan, Pahang. The data was collected using a set of questionnaires adapted from National Health and Morbidity Survey (NHMS). Blood sample was obtained to determine the hs-CRP level. Kruskal-wallis test was used to determine the association between the variables. Results There was no significant association between hs-CRP level and the time spent on sitting per day [H(2) = 1.878, p = 0.391], with a mean rank of 37.67 mg/L for sitting time less than 1 hour, 40.92 mg/L for sitting time 1-3 hours and 32.71 mg/L for sitting time more than 4 hours. Conclusions This study concludes that the hs-CRP level was not influenced by the sitting time per day of the obese women. This study can be baseline data for healthcare professionals and develop awareness platform on maintaining normal body mass index among women.